FACTORS RELATED TO THE RESPONSE TIME OF NURSING IN EMERGENCY PATIENTS MANAGEMENT - Saktiawati Saktiawati; Silvah Silvah; M. Irsan Arief Ilham (Homes Journal = Hospital Management Studies Journal, 2021)
Background:One indicator of the successful prevention of medical emergency patients is the response time of health workers. Response time A fast will reduce the incidence of death by about 30%, on the other hand, if the delayed response time is will have an adverse impact, resulting in permanent disability and death.Objective:This study aims to determine the factors related to the response time of nurses in handling emergencies in the Emergency Room(IGD), Operating Room (OK), and Intensive Care Unit (ICU) at Ilagaligo East Luwu Hospital 2020. Method: Thestudy is a cross-sectional study. The population in this study were all nurses in the IGD, OK, and ICU Lagaligo I Hospital, East Luwu. The sampling technique was total sampling with a total of60 nurses.Result:The results showed that there was a relationship (p-value <0.034) between education (p = 0.05), years of service (p = 0.016), and training (p = 0.034) with the response time of nurses at Lagaligo I Hospital in 2020. It is hoped that the hospital will continue to encourage staff/employees, in this case, nurses, to continue their education and continuous training to support the professionalism of all nurses. Conclusion:The incidence of the response time of slownurses in patients is due to the absence of good cooperation with the patient's family.It is hoped that the hospital will provide support and motivation to nurses to improve their education by existing standards.